Reader’s perception and translator’s adaptation strategies of cultural humor in the English translation of The Scholars - Syed Abdullah, Syed Nurulakla; Abdullah, Muhammad Alif Redzuan; Li Ne, . (Persatuan Linguistik Malaysia, 2024)
Abstract Due to linguistic and cultural differences, translating Chinese humour into English has always been a challenging task. This study primarily assesses whether translators successfully convey humour in their translation by evaluating readers' perception of humour in the translated text, thus achieving cultural transmission and communication. The research data is drawn from the cultural humour of the Chinese humorous novel Rulin Waishi and its English translation The Scholars. Using a questionnaire survey, the study examines readers' perceptions of cultural humour in the translated text. Using Verschueren's adaptation theory, the study applies a qualitative method to investigate the translation strategies from four aspects: structural adaptation, contextual adaptation, dynamic adaptation, and salience in the adaptation process, with the aim of transferring both the surface and deep cultural meanings of Chinese humour into English. The results of the survey show that almost all readers believe that the translator has successfully transferred the cultural humour of the original text into the translated version. In addition, during the adaptation process, the translator employed specific translation techniques such as transcoding (with or without explanation), paraphrasing, omission, and substitution. These methods were dynamically applied to adapt the source text to the target language at both the formal and contextual levels, ensuring the humour of the original was conveyed more effectively. This study offers English-speaking readers an opportunity to appreciate Eastern humour, whilst deepening their understanding of Chinese humourous literature.